The Relationship between Vitamin D, Body Mass Index and some Dietary Products with Acne Vulgaris; A Case-Control study in Baghdad/Iraq - Zalzala, Sarah Haider; Ali, Besmah Mohammad; Fahad, Zahraa Saeed (Journal of Contemporary Medical Sciences, 2024)
Objective: To investigate the association of vitamin D level and moderate to severe acne as a primary outcome, and its association with BMI, dairy products, and chocolate consumption. Subjects and Methods: A case-control study was conducted in a dermatology outpatient clinic. Patients, diagnosed with moderate to severe acne vulgaris that warrant treatment with oral antibiotics, and had global acne grading system (GAGS) score of >=19 were eligible to be selected as cases. Aged matched, with no or mild cases of acne were eligible to be selected as controls. The participant height, weight, BMI, and serum circulating 25-hydroxyvitamin D level were measured. A modified food frequency questionnaire was used for dietary history. Results: Comparing Cases (N = 101) and Control (N = 134), the mean of vitamin D level in cases were lower than that in the controls, however no statistically significant difference is observed. There were statistically insignificant differences between the studied groups regarding milk (whole, low fat, skimmed and any type of milk), cheese, yogurt, other dairy products, and chocolate consumption. However, a statistically significant disparity in weight is noted, but not in BMI. Conclusion: The results did not reveal any statistically significant associations between vitamin D level, BMI, dairy and chocolate consumption, and moderate to severe acne. However, it is important to note that this does not definitively rule out the possibility of any potential relationships or effects.